2018
DOI: 10.1186/s13756-018-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of surgical antimicrobial prophylaxis in laparoscopic surgery: a before-after study

Abstract: BackgroundThe optimal timing of preoperative surgical antimicrobial prophylaxis (SAP) remains uncertain. This study aimed to evaluate the impact of changing the timing of SAP on the incidence of surgical site infection (SSI) in laparoscopic surgery.MethodsWe performed a before-after study from August 2014 through June 2017 to assess the impact of changes in the timing of SAP on the incidence of SSI at a 790-bed tertiary care center in Japan. The intervention was the administration of SAP immediately after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…27 From an organizational perspective, it has been shown that the completion of SAP administration was greater than 98%, and, therefore, very reliable if given immediately after entering the operating room. 15 Although our primary exposure variable was the exact timing of SAP administration, our data confirm findings from many previous studies [4][5][6]20,21,28 that other confounders are significantly associated with SSI risk: higher ASA score, clean-contaminated wound classes (vs clean), and surgical procedures exceeding standard time were associated with an increased risk, as shown elsewhere.…”
Section: Principal Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…27 From an organizational perspective, it has been shown that the completion of SAP administration was greater than 98%, and, therefore, very reliable if given immediately after entering the operating room. 15 Although our primary exposure variable was the exact timing of SAP administration, our data confirm findings from many previous studies [4][5][6]20,21,28 that other confounders are significantly associated with SSI risk: higher ASA score, clean-contaminated wound classes (vs clean), and surgical procedures exceeding standard time were associated with an increased risk, as shown elsewhere.…”
Section: Principal Findingssupporting
confidence: 87%
“…Our main results indicating administration of SAP close to the time incision are supported by pharmacokinetic data showing mean serum concentration peaks already 3 minutes after intravenous cefuroxime administration and a half-life of 30 minutes . From an organizational perspective, it has been shown that the completion of SAP administration was greater than 98%, and, therefore, very reliable if given immediately after entering the operating room …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation